The Effect of Digital Competence on Improving Teacher Performance: A Case of Harapan Christian Vocational School in Rantepao - Agustinus Palimbong; Mesta Limbong; Witarsa Tambunan (Budapest International Research and Critics University, 2022)
The problem at SMK Kristen Harapan Rantepao is the low performance of teachers in learning. To improve teacher performance, it is necessary to analyze and prove the factors causing the low performance of the teacher. Many factors can affect teacher performance, but this study only focuses on examining